Wonder Findings of Number of Cells in a Body Including Sexual Cells, Remedy of Corona Virus, Increase of Memory, and other Cells by Couple System (Global Journal of Science Frontier Research, 2020)
Abstract not found
Keywords: number of cells related to couple system; sexual activity; corona virus; cancer cells; neurons of humans; cause of diseases; memory cells